THE BETA ROLE IN AFFECTING STOCK RETURNS WITH UNCONDITIONAL AND CONDITIONAL APPROACHES (Case Study of Companies Listed in the LQ 45 Index) - Murtiadi Awaluddin; Dewi Pratiwi; Rulyanti Susi Wardhani (Universitas Islam Negeri Alauddin Makassar, 2019)
This study aims to determine the effect of beta on return by using two unconditional and conditional approaches. In this study a sample of companies listed on the Indonesia Stock Exchange used the LQ 45 Index for the period January 2011 to December 2015. From the tests obtained results showed that in the unconditional beta approach the stock had a positive and insignificant effect on stock returns. Whereas by using a conditional approach, the results obtained where beta and return have a significant positive effect when the positive risk premium and a positive effect are not significant when the risk premium is negative.Keyword: Beta, Return, Risk Premium, Unconditional, Conditional.